2016
DOI: 10.1007/s12288-016-0706-7
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Cyclosporine Monotherapy in Patients of Aplastic Anemia: Experience of a Tertiary Care Hospital in Eastern India

Abstract: Introduction Immune suppression is a crucial pillar for treatment of aplastic anemia. Cyclosporine monotherapy is an easily available, affordable therapeutic option with good safety profile. Methods and Materials This prospective study was conducted over a period of 2 years from June 2012 to July 2014. The diagnosis and response to treatment of aplastic anemia was established as per published criteria. Follow up was done at 3 and 6 months in order to assess the response. Results 57 patients of acquired aplasti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…A study by Maschan et al in pediatric patients showed overall response rate (ORR) (CR + PR) of 45% with CsA monotherapy [64]. In another study of CsA monotherapy use in 57 patients from India, the ORR was 19.6% at 6 months; the median age was 37 years (range 6-81 years) [65]. A study from Yemen resulted in 14.3% CR and 35.7% PR at 6 months and 78.6% OS at 1 year [63].…”
Section: Cyclosporine Monotherapymentioning
confidence: 98%
“…A study by Maschan et al in pediatric patients showed overall response rate (ORR) (CR + PR) of 45% with CsA monotherapy [64]. In another study of CsA monotherapy use in 57 patients from India, the ORR was 19.6% at 6 months; the median age was 37 years (range 6-81 years) [65]. A study from Yemen resulted in 14.3% CR and 35.7% PR at 6 months and 78.6% OS at 1 year [63].…”
Section: Cyclosporine Monotherapymentioning
confidence: 98%
“…In addition, several previous studies have elucidated that treatment with CsA may increase the number of Tregs in patients with AA and other diseases ( 42 44 ). Previous studies have indicated good efficacy of CsA in the treatment of patients with AA, which may indicate that if it existed, the inhibition of Tregs by CsA may be limited and does not interfere with the treatment effect ( 1 , 45 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…10 Despite obvious efficacy and good safety profile of eltromobopag, cost remains a concern .Similarly cost and availability of horse ATG remains a hurdle to its use in developing countries. In such cases, combination of rATG with CSA 11 or CSA alone remain reasonable alternatives 12 .…”
Section: Introductionmentioning
confidence: 99%